Factors affecting the length of center release time in a baby in Pakong Village, Pakong Sub-District, Pamekasan District - Qurratul A'yun; Yayuk Eliyana; Layla Imroatu Zulaikha (Alma Ata University Press, 2021)
Bacground: Maternal and perinatal health problems are national problems that need and receive top priority, because they greatly determine the quality of human resources for future generations. Various efforts have been made to prevent neonatal mortality, which prioritizes the maintenance of pregnancy as well as possible, delivery assistance according to service standards and adequate newborn care including hygienic umbilical cord care.Objectives: The goal of doing umbilical cord care is to prevent neonatal infection, because this is the most vulnerable period for babies. As for the indicators that affect the release of the remaining umbilical cord, apart from being influenced by the care of the umbilical cord by keeping the umbilical cord dry and clean. Also influenced by the mother's compliance to clean the umbilical cord every day. Maternal hygiene when caring for the umbilical cord and the frequency of changing diapers every time the diaper is dirty and wet, and influenced by how to care for the umbilical cord, namely with sterile gauze, 70% alcohol gauze or 10% povidone. The duration of the release of the remaining umbilical cord varies, namely within 3 days, 5 days, 7 days, some up to 2 weeks.Methods: Based on the research objectives, the research design used in this research is quantitative analytic, namely research that aims to determine the relationship between two or more variables with the data collection process which is only done once for each research variable. The approach used is cross sectional, namely research in which the independent variables and the dependent variable are measured simultaneously and carried out briefly or once. The independent variables in this study are how to care for the umbilical cord, humidity of the umbilical cord, environmental sanitation conditions. As for the dependent variable, namely the length of time to release the umbilical cord. The measuring instruments used in this study were questionnaires and checklists. Result: The results showed that there was a significant effect between umbilical cord care and length of time to disconnect the umbilical cord with a value of p = 0.000. Conclusions: there are several efforts that need to be considered. For the respondents, it is hoped that the mother will not only get information about umbilical cord care, but also learn about proper umbilical cord care.